Development and user-testing of a digital patient decision aid to facilitate shared decision-making for people with stable angina - Emma Harris; Dwayne Conway; Angel Jimenez-Aranda; Jeremy Butts; Philippa Hedley-Takhar; Richard Thomson; Felicity Astin (BMC Medical Informatics and Decision Making, 2022)
Abstract Background Research shows that people with stable angina need decision support when considering elective treatments. Initial treatment is with medicines but patients may gain further benefit with invasive percutaneous coronary intervention (PCI). Choosing between these treatments can be challenging for patients because both confer similar benefits but have different risks. Patient decision aids (PtDAs) are evidence-based interventions that support shared decision-making (SDM) when making healthcare decisions. This study aimed to develop and user-test a digital patient decision aid (CONNECT) to facilitate SDM for people with stable angina considering invasive treatment with elective PCI. Methods A multi-phase study was conducted to develop and test CONNECT (COroNary aNgioplasty dECision Tool) using approaches recommended by the International Patient Decision Aid Standards Collaboration: (i) Steering Group assembled, (ii) review of clinical guidance, (iii) co-design workshops with patients and cardiology health professionals, (iv) first prototype developed and ‘alpha’ tested (semi-structured cognitive interviews and 12-item acceptability questionnaire) with patients, cardiologists and cardiac nurses, recruited from two hospitals in Northern England, and (v) final PtDA refined following iterative user-feedback. Quantitative data were analysed descriptively and qualitative data from the interviews analysed using deductive content analysis. Results CONNECT was developed and user-tested with 34 patients and 29 cardiology health professionals. Findings showed that CONNECT was generally acceptable, usable, comprehensible, and desirable. Participants suggested that CONNECT had the potential to improve care quality by personalising consultations and facilitating SDM and informed consent. Patient safety may be improved as CONNECT includes questions about symptom burden which can identify asymptomatic patients unlikely to benefit from PCI, as well as those who may need to be fast tracked because of worsening symptoms. Conclusions CONNECT is the first digital PtDA for people with stable angina considering elective PCI, developed in the UK using recommended processes and fulfilling international quality criteria. CONNECT shows promise as an approach to facilitate SDM and should be evaluated in a clinical trial. Further work is required to standardise the provision of probabilistic risk information for people considering elective PCI and to understand how CONNECT can be accessible to underserved communities.